Temporomandibular disorders and parafunctional oral habits: an anamnestic study - Melissa de Oliveira Melchior; Marcelo Oliveira Mazzetto; Cláudia Maria de Felício (Dental Press Editora, 2012)
OBJECTIVE: To assess the frequency and severity of the signs and symptoms of temporomandibular disorders (TMD), the frequency of parafunctional oral habits and the correlation between the variables by means of the patients' perception regarding their problem. METHODS: One hundred patients diagnosed with TMD, through a clinical examination of their masticatory system, answered the questions of a previously published protocol concerning the signs and symptoms most frequently reported in the literature. RESULTS: According to the results from the non parametric statistical analysis, the frequency for the following signs and symptoms was significant: Fatigue and muscle pain, joint sounds, tinnitus, ear fullness, headache, chewing impairment and difficulty to yawn (p<0.01) and otalgia (p<0.05). As to the parafunctional oral habits, there was a significant presence of teeth clenching during the day and night (p<0.01) and teeth grinding at night (p<0.05). The variable correlation analysis showed that there was a positive correlation between symptom frequency and severity; age was correlated with the presence of otalgia, cervical pain and teeth sensitivity, besides being correlated with muscle and joint pain severity. Habit frequency was negatively correlated with age. TMD duration was also positively correlated with the symptoms of tinnitus, ear fullness, muscle and joint pain. CONCLUSION: The study results showed that the anamnestic assessment using ProDTMMulti can predict the severity of the TMD case.